Are Campaign Promises Effective? - Michael Ganslmeier (ZBW - Leibniz Information Centre for Economics, 2023)
In democracies, political parties promise to expand social benefits to attract voters in the lead-up to elections. However, we know relatively little whether such campaign promises effectively sway benefiting voters. Using a regression-discontinuity design, we estimate the causal effects of an electoral pledge made by the German conservative party to expand pension benefits ahead of the parliamentary election in 2013. The results show that the promise increased alignment with the pledge-making party by 12.2% among eligible beneficiaries. These gains originate from the re- alignment of individuals who traditionally support left-wing platforms, while it had no mobilizing effect on inactive voters. In addition, we find that the pledge effect is larger among individuals with lower economic and social security. Finally, the policy-induced alignment gain is transitory as it disappears once the pledge is fulfilled. Overall, our paper shows that electoral pledges related to social benefits are rather temporarily persuasive than permanently mobilizing.
Keywords: D72; D91; H55; I38; 330; campaign promises; electoral pledges; social benefits; policy feedbacks; prospective voting